(untitled) (Journal of the College of Education for Women, 2019)
Air pollution is one of the complex problems plaguing the environment at the present timeas a result of many liberation of gases, vapors and fumes of fuels and chemicals resultingfrom industrial activities . It should be noted that there are some elements of the heavy (HeavyMetals), including toxic in the air, with different concentrations in the air depending on thenature of the area, for example be in rural areas is lower than in cities or industrial areas asmeasured parts million (ppm ) or parts per billion (ppb). Some of these important elements inthe physiological processes and enzymatic organisms but become toxic and Qatlhand-increaseTercisahaan the permissible limits Bhave nature ,The air contaminant containing the lingeringminutes, lead and heavy metals have bad effects on human health, causing various diseases.So the goal of this study to know Atrthelot the air in minutes lingering element lead on humanhealth through to identify the causes of serious air pollution first and then the impact of all ofthe outstanding minutes and lead to human health.